Possible Corruption Risks to Successful Implementation of REDD+ in Bangladesh (The Chittagong University Journal of Science, 2021)
Deforestation and forest degradation are the important causal agents to global climate change. REDD+ (Reducing Emissions from Deforestation and Forest Degradation along with conservation and enhancement of forest carbon stocks and sustainable management of forest) is a recently adopted global initiative to mitigate global climate change by conserving the forests and its carbon. Bangladesh is still in the preparatory phase of the REDD+ program. Assessing the potential risks of corruption is important to the setting up of strategies of REDD+ implementation. So, a study was conducted in the Madhupur, Sreemangal and Rangamati forest areas to assess these risks. The study was conducted through three types of surveys and interviews. It was found that there is a chance of potential corruption risks while implementing REDD+ program in Bangladesh. Political leaders and other powerful groups may manipulate the policy making and development strategies of REDD+. Financial management, benefit sharing and procurement management in the REDD+ program should be considered in the corruption risks analysis. There is a chance of diversion or embezzlement of REDD+ funds, laundering of money and elite capture of REDD+ benefits. Over estimation of costs and collusions in the bidding may also occur while implementing REDD+. For the successful and transparent implementation of REDD+, this possible risks should be taken into consideration. This study can be partially useful to fixing up the REDD+ strategies in Bangladesh.The Chittagong Univ. J. Sci. 40(1) : 1-20, 2019